The Effect of a Drying Time and The Different of Storage Periods to The Quality and The Shelflife of Milkfish (Chanos chanos forsk.) Cooked by High-Pressure Cooker - Nurul Meutia Agustiari; Ratna Ibrahim; Titi Surti (Indonesian Association of Food Technologists, 2018)
Milkfish that have been seasoned with some spices then cooked by a high -cooker produced a fish product which has soft spines and bones. The product which has a local name bandeng presto has been popular in Indonesia due to the product is tasty and it is easier to be consumed directly after it is prepared as a dish. The storage life of bandeng presto is relatively short, which is due to deterioration process by microbes after processing. Consequently, this condition can retard the products distribution. The aims of the research are to understand is there any significant influence of differing the drying time (0 hours and 4 hours) of milkfish cooked by a high-pressure cooker by using an electric oven (50oC) and storage period at room temperature (5 days) and also to find out which treatment produce the best product quality. The results showed that the treatment of differing the drying period gave a highly significant influence (P <0.01) on the sensory value and the moisture content but did not gave significant influence (P >0.05) on the number of bacteria colonies. The length of storage period gave a highly significant influence (P <0.01) on the sensory value between the products which were dried for 4 hours and without drying treatment but only the drying process for 4 hours gave a highly significant influence (P <0.01) on the moisture content, the water activity and the number of bacteria colonies. The quality of the products that were dried for 4 hours were better and their storage life can reach up to 3 days compared to the products that were not dried.Keywords: Milkfish, high pressure cooker, drying, oven, quality, storage life